2002
DOI: 10.1021/es015693d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Starvation on the Performance and Re-acclimation of Biotrickling Filters for Air Pollution Control

Abstract: Biotrickling filters for air pollution control are expected to encounter fluctuating conditions or periods without pollutant supply. In the present study, we investigated the effect of pollutant starvation in bench-scale biotrickling filters treating toluene. The experimental protocol consisted of starving biotrickling filters under various conditions: with or without airflow, with or without liquid recycle, and with or without an alternate carbon source (glucose) supply. The duration of the period without tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 28 publications
(44 reference statements)
4
58
0
Order By: Relevance
“…Published data related to the behavior of BTFs under typical perturbations in industry (e.g., cyclic pollutant feeding, variable inlet concentration, starvation periods, and shutdowns) are relatively scarce. 23,24 Successful reacclimation of toluene-degrading BTFs has been reported after periods of up to 9 days of non-use, 25 and ethyl acetate removal in a peat biofilter after a non-use period of as much as 15 days. 26 In addition, it has been reported 8,27,28 that a buffering carbon filter installed preceding biological reactor facilitates the treatment of sudden variations in concentration, spikes, and unstable loads of VOCs.…”
Section: Technical Papermentioning
confidence: 99%
“…Published data related to the behavior of BTFs under typical perturbations in industry (e.g., cyclic pollutant feeding, variable inlet concentration, starvation periods, and shutdowns) are relatively scarce. 23,24 Successful reacclimation of toluene-degrading BTFs has been reported after periods of up to 9 days of non-use, 25 and ethyl acetate removal in a peat biofilter after a non-use period of as much as 15 days. 26 In addition, it has been reported 8,27,28 that a buffering carbon filter installed preceding biological reactor facilitates the treatment of sudden variations in concentration, spikes, and unstable loads of VOCs.…”
Section: Technical Papermentioning
confidence: 99%
“…14 Some studies reported biofilter performance under chemical starvation conditions. 11,13,15,16 Fitch et al studied biofiltration for 1-butanol removal under continuous and diurnal loading conditions and reported that diurnal operation did not contribute to a decrease in biofilter efficiency as compared with continuous operation. 13 Most of these studies were concerned mainly with the reacclimation periods and the duration and mode of starvation.…”
Section: Technical Papermentioning
confidence: 99%
“…where N is the total number of corresponding data points, and x (1) and x (2) represent corresponding properties of interest.…”
Section: Report Documentation Pagementioning
confidence: 99%